The Effect Of Village Service Information Systems On Community Satisfaction In Gidosebua Village, Gunungsitoli Idanoi District, Gunungsitoli City, North Sumatra Province - Dippos Pasaribu; Ibnu Rasyid Munthe; Syaiful Zuhri Harahap; Angga Putra Juledi (International Journal of Health Engineering and Technology, 2026)
This study aims to analyze the effect of the Village Service Information System on community satisfaction in Gidosebua Village, Gunungsitoli Idanoi District, Gunungsitoli City. The development of information technology encourages village governments to improve the quality of administrative services through the implementation of information systems that are more effective, efficient, transparent, and accountable. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to residents who had received administrative services at the Gidosebua Village Office. The independent variable in this study was the Village Service Information System, while the dependent variable was community satisfaction. Data analysis was conducted using validity tests, reliability tests, simple linear regression analysis, t-tests, correlation coefficient analysis, and coefficient of determination. The results of this study are expected to provide an overview of the influence of information system implementation on improving the quality of public services and serve as an evaluation reference for the village government in enhancing technology-based administrative services.